Antigen-Presenting B Cells Program the Efferent Lymph T Helper Cell Response - Alsén, Samuel; Cervin, Jakob; Deng, Yaxiong; Szeponik, Louis; Wenzel, Ulf Alexander; Karlsson, Joakim; Cucak, Helena; Livingston, Megan; Bryder, David; Lu, Qianjin; Johansson-Lindbom, Bengt; Yrlid, Ulf (Frontiers in Immunology, 2022)
B cells interact with T follicular helper (Tfh) cells in germinal centers (GCs) to generate high-affinity antibodies. Much less is known about how cognate T–B-cell interactions influence Th cells that enter circulation and peripheral tissues. Therefore, we generated mice lacking MHC-II expressing B cells and, by thoracic duct cannulation, analyzed Th cells in the efferent lymph at defined intervals post-immunization. Focusing on gut-draining mesenteric lymph nodes (MLNs), we show that antigen-specific α4β7+ gut-homing effector Th cells enter the circulation prior to CXCR5+PD-1+ Tfh-like cells. B cells appear to have no or limited impact on the early generation and egress of gut-homing Th cells but are critical for the subsequent appearance of Tfh-like cells that peak in the lymph before GCs have developed. At this stage, antigen-presenting B cells also reduce the proportion of α4β7+ Th cells in the MLN and efferent lymph. Furthermore, cognate B-cell interaction drives a broad transcriptional program in Th cells, including IL-4 that is confined to the Tfh cell lineage. The IL-4-producing Tfh-like cells originate from Bcl6+ precursors in the LNs and have gut-homing capacity. Hence, B cells program the efferent lymph Th cell response within a limited window of time after antigenic challenge.